Efektivitas Metabolit Sekunder Pseudomonas sp. dan Bacillus sp. Sebagai Pengendali Meloidogyne incognita - Vanya Yuni Artafirdaus Sabilillah (Fakultas Pertanian Universitas Jember, 2025)
Root knot nematodes (Meloidogyne incognita) are one of the common pathogens that attack tomato plants. Tomato plants (Solanum lycopersicum L.) are one of the important horticultural commodities in Indonesia. Controlling root knot nematodes using biological agents consisting of bacteria and fungi is an environmentally friendly alternative compared to the use of chemical pesticides. Groups of bacteria that are commonly used as biological control agents for root knot nematodes include Pseudomonas sp. and Bacillus sp. This study aims to determine the effectiveness of secondary metabolites of Pseudomonas sp. and Bacillus sp. as a controller of Meloidogyne incognita. This study used a Completely Randomized Design (CRD) with a single factor, namely, Pseudomonas sp. and Bacillus sp. These factors consist of 4 treatments and 6 replications so that there are 24 experimental units. The variables observed were J2 mortality M. incognita. The results showed that the highest average at 24 hours was obtained from the treatment of Pseudomonas sp. and Combination with the same value of 8,7%. At 96 hours and 168 hours the highest average was obtained from the Pseudomonas sp. treatment with values of 55.8% and 91%.
uploud by Tedyy_14.04.2026
Keywords: Root Knot Nematodes; Secondary Metabolites; Nematicidal